Analysis of Sustainability of Shallot Farming in Pabedilan District, Cirebon Regency - Salsabila, Tiara Yuniar; Ismi, Keysha Alea; Nurmaningsi, Risti; Dwirayani, Dina (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the level of sustainability of shallot farming in Pabedilan District, Cirebon Regency, based on three main dimensions, namely economic, social, and environmental. Shallots are a superior horticultural commodity that contributes significantly to farmers' income, but their sustainability faces various challenges. The method used in this study is composite index analysis, with 30 respondents selected purposively. The results of the study indicate that the economic dimension is in the fairly sustainable category, the social dimension is in the sustainable category, and the environmental dimension is still at a less sustainable level. Factors that influence sustainability include limited access to capital, lack of diversification of information sources, and the use of chemical agricultural inputs which is still high. Therefore, it is necessary to strengthen the capacity of farmers through continuous training and facilitation of access to environmentally friendly technology to improve the sustainability of shallot farming as a whole.